Functional Outcome Following Stroke Thrombectomy in Clinical Practice. Issue 9 (September 2019) - Wollenweber, Frank A.; Tiedt, Steffen; Alegiani, Anna; Alber, Burkhard; Bangard, Christopher; Berrouschot, Jörg; Bode, Felix J.; Boeckh-Behrens, Tobias; Bohner, Georg; Bormann, Albrecht; Braun, Michael; Dorn, Franziska; et al.
Abstract : Background and Purpose—: Endovascular treatment for large vessel occlusion in ischemic stroke has proven to be effective in large clinical trials. We aimed to provide real-world estimates of endovascular treatment reperfusion rates and functional outcome on a countrywide scale. Methods—: Two thousand seven hundred ninety-four patients with large vessel occlusion were included into an investigator-initiated, industry-independent, prospective registry in 25 sites in Germany between June 2015 and April 2018. The primary outcome was the score on the modified Rankin Scale ranging from zero (no symptoms) to 6 (death) at 3 months. Secondary analyses included the prediction of a good outcome (modified Rankin Scale, 0–2). Dichotomized analyses of predictors were performed using logistic regression adjusted for potential confounders. Results—: Median age was 75 years (interquartile range, 64–82); median National Institutes of Health Stroke Scale score was 15 (interquartile range, 10–19). Vessel occlusion was in the anterior circulation in 2265 patients (88%) and in the posterior circulation in 303 patients (12%). Intravenous alteplase before endovascular treatment was given in 1457 patients (56%). Successful reperfusion was achieved in 2143 subjects (83%). At 3 months, 854 patients (37%) showed a good outcome; mortality was 29%. There was no difference between anterior and posterior circulation occlusions ( P =0.27). Significant predictors for a good outcome were younger age (odds ratio [OR], 1.06; 95% CI, 1.05–1.07), no interhospital transfer (OR, 1.39; 95% CI, 1.03–1.88), lower stroke severity (OR, 1.10; 95% CI, 1.08–1.13), smaller infarct size (OR, 1.26; 95% CI, 1.15–1.39), alteplase use (OR, 1.49; 95% CI, 1.08–2.06), and reperfusion success (OR, 1.69; 95% CI, 1.45–1.96). Conclusions—: High rates of favorable outcome can be achieved on a countrywide scale by endovascular treatment. Mortality appears to be greater in the daily routine than otherwise reported by authors of large randomized trials. There were no outcome differences between the anterior and posterior circulation. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03356392. Abstract : Supplemental Digital Content is available in the text.